The conflicting role highlights the complexity of GSDMs in cancer - He, Sijia; Huang, Qian; Cheng, Jin (Frontiers in Immunology, 2025)
Gasdermins (GSDMs) are an important family of proteins that have received extensive attention in tumor research in recent years. They directly induce tumor cell death by mediating pyroptosis and also regulate the recognition and clearance of tumor cells by the immune system by affecting the microenvironment. Therefore, it is of great significance to investigate the role of GSDMs in tumor development and tumor microenvironment. It can not only reveal new mechanisms of cancer development, but also provide theoretical basis for the development of novel anti-tumor therapeutic strategies. This literature review aims to systematically summarize the dual roles of GSDMs in tumor development and their interactions with the tumor microenvironment, and to focus on the importance of GSDM-mediated pyroptosis in anti-cancer therapy, with a view to providing guidance for future research directions.